1991
DOI: 10.1029/90jb01904
|View full text |Cite
|
Sign up to set email alerts
|

A Cretaceous pole from south China, and the Mesozoic hairpin turn of the Eurasian apparent polar wander path

Abstract: To contribute to the apparent polar wander path (APWP) of the South China Block and Eurasia in general, we collected paleomagnetic samples from Mesozoic red beds around the city of Ya' an (30°N, 103°E) in the western tip of the Sichuan Basin. In this paper we present the results from 373 oriented cores taken from one section representing 3 km of sedimentary rocks. The section is dated with continental ostracods and with a magnetostratigraphic correlation between a densely sampled 272‐m sequence and the polarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Location is shown on Figures 1 and 11. strata is well known with magnetic-polarity stratigraphy (Zhuang et al, 1988;Enkin et al, 1991) and biostratigraphic data (BGMRSP, 1991;Gu and Liu, 1997), we interpret the main growth interval to lie between the near-top Cretaceous and the Oligocene. Eastward, only poorly developed growth strata are observed in seismic profiles, including some unclear reflectors that onlap the forelimbs of the anticlines.…”
Section: The South Longmen Shanmentioning
confidence: 84%
“…Location is shown on Figures 1 and 11. strata is well known with magnetic-polarity stratigraphy (Zhuang et al, 1988;Enkin et al, 1991) and biostratigraphic data (BGMRSP, 1991;Gu and Liu, 1997), we interpret the main growth interval to lie between the near-top Cretaceous and the Oligocene. Eastward, only poorly developed growth strata are observed in seismic profiles, including some unclear reflectors that onlap the forelimbs of the anticlines.…”
Section: The South Longmen Shanmentioning
confidence: 84%
“…Good correlation among the amount of inclination flattening, the degree of anisotropy and sedimentary facies indicates that the depositional processes produced the observed shallow inclination in the Yichang area. Because the far‐sided pole position (78.6°N, 273.4°E, dp / dm = 2.4°/4.1°) is reported from Cretaceous red beds in the Sichuan basin in the SCB (Otofuji et al 1990; Enkin et al 1991a,b), further palaeomagnetic and rock magnetic studies are required to study the shallowing effect in this basin.…”
Section: Discussionmentioning
confidence: 99%
“…1, locality-based variation in inclination shallowing has been observed in the Cretaceous red beds of the South China Block (SCB). Although, inclination shallowing has not been detected in the coastal area of the SCB (Morinaga & Liu 2004;Zhu et al 2006), anomalously large shallowing has been reported from the Sichuan Basin of the same block (Otofuji et al 1990;Enkin et al 1991a). Following these observations, demand for further investigations became high to trace local origin of the inclination shallowing.…”
Section: Introductionmentioning
confidence: 97%
“…2006), anomalously large shallowing has been reported from the Sichuan Basin of the same block (Otofuji et al . 1990; Enkin et al . 1991a).…”
Section: Introductionmentioning
confidence: 99%